(untitled) (Communication & Society, 2009)
In this article, we intend to set out the results of a study on how humour is received in a locally produced situation comedy. Through this work, we have been trying to understand what social and cultural representations would be recognised by the audience in the show as accurate reflections of themselves and their cultural and social context, as well as which they would reject. In order to carry out this analysis we have used qualitative methodology; intending, through discussion groups, to understand the consumption of humour in a sitcom produced by a television station serving the autonomous region of Catalonia. This article ratifies the idea that humour is determined socially and culturally; knowledge which allows us to identify the philias and phobias which the subjects expressed with regards to humour in sitcoms. We outline the fundamental role that humour plays as a device that generates, invigorates, reinforces and/or discards elements associated with identity. Humour is used to create social connections as well as social divisions, becoming a kind of cultural mediator that generates suggestions for meaning. Our final aim is to encourage further research, within the communications area, which would have as its object the consumption, use and appropriation of the humour present in media content.